Just Stab Me Now - Bearup, Jill ([Place of publication not identified] :bSword Lady Books, 2024)
"Caroline Lindley is determined that her new romance novel will be her best one yet. Fantasy! Formal gowns! Fencing! And, of course, a twentysomething heroine to star in an enemies-to-lovers plot with all of Caroline's favourite tropes. But Lady Rosamund Hawkhurst is a thirty-six-year-old widow with a war to stop and two children to get home to and flatly refuses to take the correct approach to there being Only One Bed. What's an author to do? Especially when discussions with her editor might reveal that he and Rosamund's Hot Enemy have some suspicious similarities. Based on her popular Fantasy Heroine YouTube Shorts series, Jill Bearup's debut novel brings us the best of worlds both meta and medieval-inspired as enemies-to-BFFs Rosamund and Caroline learn what it means to be the hero of your own story. Swords optional."--Publisher's description.
Keywords: Women heroes -- Fiction; Women authors -- Fiction; Middle Ages -- Fiction; Fantasy fiction; Romance fiction; Humorous fiction